(untitled) (Hekima Review, 2006)
growth of Christianity. This has led some scholars to affirm that the centre of Christianity has shifted to the southern continents of which Africa is a part. Some African countries celebrated few years ago the centenary anniversary of evangelization. The celebrations were accompanied by an admiration of the speed with which African conversions to Christianity were made, and congratulations went to the missionaries for the large number of converts they achieved.